Encyclopedia britannica. Micropedia VOL. 10. / William Benton - Benton, William (1977)
Cross refences appear often, identified by see also, or as related entries, and always refer to other entries in the ready reference and index in alphabetical order volumes 1-x; entries are alphabetized as if the were one word, up to the comma, regardless of the number of words in the title, thus; directions, or index references, are given to the page in the macropedia (vol 1 19) on which a subject or aspect of a subject may be found in the longer articles; volume and page numbers immediately follow the title of an entry always refer to a comprehensive articles in volumes 1through19, all other volume and page references follow the text and cit sections of the longer (macropadia9) articles.